2020
DOI: 10.1097/gox.0000000000002565
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Virtual Surgical Planning for Reduction Cranioplasty

Abstract: Summary: Hydrocephalic macrocephaly may occur as a result of untreated hydrocephalus. Reduction cranioplasty is the treatment of choice for these patients when the weight of their head interferes with normal development and negatively impacts quality of life. However, this procedure has several associated risks, including prolonged anesthesia, significant blood loss, and death. Virtual surgical planning (VSP) has been shown to be a useful adjunct for orthognathic and craniofacial surgery. The follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…8 Saleh et al also found that use of VSP in procedures such as reduction cranioplasty for macrocephaly decreases irregularities seen with free handed osteotomies and thus allows for improved aesthetic results. 9 Similarly, Day et al found utility of VSP in craniomaxillofacial trauma, especially in patients with multiple failed attempts at open reduction and internal fixation. Not only did VSP allow for virtual simulation of the surgery, it also allowed for physical simulation of the operation by utilizing 3D printed skull models based on preoperative CT scans.…”
Section: Discussionmentioning
confidence: 93%
“…8 Saleh et al also found that use of VSP in procedures such as reduction cranioplasty for macrocephaly decreases irregularities seen with free handed osteotomies and thus allows for improved aesthetic results. 9 Similarly, Day et al found utility of VSP in craniomaxillofacial trauma, especially in patients with multiple failed attempts at open reduction and internal fixation. Not only did VSP allow for virtual simulation of the surgery, it also allowed for physical simulation of the operation by utilizing 3D printed skull models based on preoperative CT scans.…”
Section: Discussionmentioning
confidence: 93%
“…3D-printed medical models (3DPMM) are an emerging product with a smart concept for medical pre-surgery planning widely spread in the health-care sector (Gibson et al , 2015; Saleh et al , 2020; Ganguli et al , 2018). A 3D-printed medical model is an entity that replicates the geometry or form of a biological structure (Yap et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A 3D-printed medical model is an entity that replicates the geometry or form of a biological structure (Yap et al , 2017). 3DPMM helps to solve complex pre-surgery planning problems that result in enhanced pre-visualizing of surgical intervention, the easy orientation of the exact defected area, deep understanding of anatomy and preparation of the proposed fixation (Lychagin et al , 2019; Saleh et al , 2020). 3DPMM finds various applications in pre-surgery planning for cranioplasty surgery, prosthetics, orthotics and dental research (Bibb et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations